Mobile genetic elements carrying aminoglycoside resistance genes in Acinetobacter baumannii isolates belonging to global clone 2 - Naderi, Ghazal; Talebi, Malihe; Gheybizadeh, Roghayeh; Seifi, Arash; Ghourchian, Sedigheh; Rahbar, Mohammad; Abdollahi, Alireza; Naseri, Abdolhossein; Eslami, Parisa; Douraghi, Masoumeh (Frontiers in Microbiology, 2023)
Aminoglycosides are used to treat infections caused by carbapenem resistant Acinetobacter baumannii (CRAB) strains. However, resistance to aminoglycosides has increased remarkably in the last years. Here, the mobile genetic elements (MGEs) associated with resistance to aminoglycosides were examined in the global clone 2 (GC2) A. baumannii. Among the 315 A. baumannii isolates, 97 isolates were identified as GC2 and 52 of GC2 isolates (53.6%) were resistant to all aminoglycosides tested. The AbGRI3s carrying the armA were detected in 88 GC2 isolates (90.7%), of them, 17 isolates (19.3%) carried a new variant of AbGRI3 (AbGRI3ABI221). The aphA6 was located in TnaphA6 of 30 isolates out of 55 aphA6-harboring isolates and 20 isolates were found to harbor TnaphA6 on a RepAci6 plasmid. The Tn6020 carrying the aphA1b was detected in 60 isolates (61.8%) and was located, all in AbGRI2 resistance islands. The pRAY* carrying the aadB gene was detected in 43 isolates (44.3%) and no isolate was found to contain a class 1 integron harboring this gene. The GC2 A. baumannii isolates contained at least one MGE carrying the aminoglycoside resistance gene, located mostly either in the chromosome within AbGRIs or on the plasmids. Thus, it is likely that these MGEs play a role in the dissemination of aminoglycoside resistance genes in GC2 isolates from Iran.